Effect of hydroponics technology on some physical indicators for the production and growth of lettuce (Damascus University Journal of agriculture sciences, 2024)
The research was carried out on Abu Jerash farm at the Faculty of Agricultural Engineering at the University of Damascus during the first season 2020-2021 and in the second season (repeating the experiment) 2021-2022. The experiment aimed to study the effect of three different hydroponics techniques: Nutritious Film Technology (NFT), Drip Irrigation System Technology (DST), the cultivation technique by immersion or floating DWC, on some chemical and physical qualitative characteristics of the two cultivars of romaine and iceberg lettuce, using three percentages of different concentrations of nutrient solutions (100%,50%,25%). The experiment began by planting lettuce seeds within seedling trays in the middle of  September and 45-50 days after planting, the seedlings enter the hydroponics system at the end of October and during the months(November and December) the plants were developed within the hydroponics technique and fed with the nutrient solution. Finally, the economic part was obtained from the crop was at the end of January, as soon as it was ripe and the solid and fused heads are formed, before the emergence of buds and flowering growths, and the elongation of the inner stem, in addition to the leaf discoloration index. The results of the variance analysis according to the tests Physiologically showed, that the treatment of hydroponics technology had a positive effect on some growth indicators of lettuce plants, as the average systems for the two hydroponics treatments NFT, DWC recorded the highest values in the indicators of saturated wet weight of leaves, dry weight of leaves, root length, leaf area, number of leaves and Leaves length compared with the average of the DST hydroponics treatment system.
Keywords: NFT; DWC; DST; Romaine And Iceberg Lettuce Cultivars; Hydroponics